a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
d(a(x)) → b(d(x))
a(x) → b(b(b(x)))
b(d(b(x))) → c(a(x))
c(x) → d(x)
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
d(a(x)) → b(d(x))
a(x) → b(b(b(x)))
b(d(b(x))) → c(a(x))
c(x) → d(x)
A(d(x1)) → B(x1)
A(x1) → B(b(x1))
B(d(b(x1))) → C(x1)
A(x1) → B(b(b(x1)))
B(d(b(x1))) → A(c(x1))
A(x1) → B(x1)
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
A(d(x1)) → B(x1)
A(x1) → B(b(x1))
B(d(b(x1))) → C(x1)
A(x1) → B(b(b(x1)))
B(d(b(x1))) → A(c(x1))
A(x1) → B(x1)
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
A(d(x1)) → B(x1)
A(x1) → B(b(x1))
A(x1) → B(b(b(x1)))
B(d(b(x1))) → A(c(x1))
A(x1) → B(x1)
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
A(d(x1)) → B(x1)
POL(A(x1)) = 2·x1
POL(B(x1)) = 2·x1
POL(a(x1)) = x1
POL(b(x1)) = x1
POL(c(x1)) = 1 + x1
POL(d(x1)) = 1 + x1
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
A(x1) → B(b(x1))
A(x1) → B(b(b(x1)))
B(d(b(x1))) → A(c(x1))
A(x1) → B(x1)
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
A(x1) → B(b(x1))
A(x1) → B(b(b(x1)))
B(d(b(x1))) → A(c(x1))
A(x1) → B(x1)
POL(A(x1)) = 14 + 4·x1
POL(B(x1)) = 4 + 4·x1
POL(a(x1)) = 7 + x1
POL(b(x1)) = 1 + x1
POL(c(x1)) = 8 + 7·x1
POL(d(x1)) = 8 + 7·x1
c(x1) → d(x1)
b(d(b(x1))) → a(c(x1))
a(x1) → b(b(b(x1)))
a(d(x1)) → d(b(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
↳ QTRS Reverse
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
a(d(x1)) → d(b(x1))
a(x1) → b(b(b(x1)))
b(d(b(x1))) → a(c(x1))
c(x1) → d(x1)
d(a(x)) → b(d(x))
a(x) → b(b(b(x)))
b(d(b(x))) → c(a(x))
c(x) → d(x)
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
d(a(x)) → b(d(x))
a(x) → b(b(b(x)))
b(d(b(x))) → c(a(x))
c(x) → d(x)